INFLUENCE OF MEDIA COMMUNICATION ON ATTITUDES AND KNOWLEDGE PREGNANT WOMEN CONSUMING FE TABLET IN THE MATERNITY CLINIC DELTA MUTIARA SIDOARJO - Faristasari, Evvin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
The effectiveness of learning and teaching processes are influenced by the precision of the use of methods and media used. The role of Fe tablet in pregnancy is very important for the health of the mother or her fetus. This research aims to know the influence of the communications media towards the knowledge and attitude to pregnant mothers in consuming Fe tablets in Maternity Clinic Delta Mutiara Sidoarjo.This type of research is a true experimental design with pretest-posttest Design. The treatment using the the extension with lectures and outreach with leaflets. The population of as many as 40 people, the sample as many as 36 people, the sampling technique used simple random sampling of each group is made up of 18 people aged 20-25 years old and high school education. Tested with Chi-Square.In the control group, pregnant women who have good knowledge score of 33,33% and obtained results of 44,44% are being received while on a group of experiments, pregnant women are knowledgeable well as much 77,78% and obtained results 93,03% of pregnant women who received. The research result obtained from X2 to calculate X2 table (7.85 5) on knowledge so Ho denied and H1 are accepted. On the attitude of expectant mothers count X2 X2 tables (4.98 3.84), so Ho denied and H1 are accepted. From the results of this research it can be concluded that there is an influence of media communication to knowledge and attitude of pregnant women to consume Fe tablets.Keywords: leaflets, Fe tablet, knowledge, attitude